Promotion and the scholarship of teaching and learning - Vardi, Iris; Quin, Robyn (Routledge, 2011)
The move toward recognizing teaching academics has resulted in the Scholarship of Teaching and Learning (SoTL) gaining a greater prominence within the academy, particularly through the academic promotions system. With several Australian universities now providing opportunities for teaching staff who do not engage in research to be promoted, it is important that the teaching criteria for promotion are demonstrably of equal value to promotion based on research. However, examination of the definitions of SoTL reveals not only their variation, but also their limitations in terms of academic promotion. This paper examines the institutional concepts underlying promotion and compares these to definitions of SoTL. It argues for a broadening of the SoTL concept to met the underlying institutional expectations of reward and recognition through promotion.